Institutional Arrangement of Financial Markets Supervision: The Case of the Czech Republic - Petr Musílek (European Financial and Accounting Journal, 2008)
The paper deals with institutional arrangement of financial supervision in the Czech Republic. Financial markets are composed of partial financial segments specialized in individual types of financial instruments and individual customer groups. Financial institutions gradually transform into financial supermarkets. There are several models of institutional arrangement of financial supervision (integrated financial supervision model, sectional financial supervision model, financial supervision within the framework of the central bank, functional model of financial supervision). Creation of financial supermarkets encourages integration of supervisory institutions, generally outside the central bank. In the Czech Republic, several versions of institutional structure of financial market supervision have been discussed in the new millennium. Final decision was implemented precipitately without deeper analysis. The supervision of the all financial market was entrusted to the Czech National Bank with close liaison between execution of monetary policy and supervisory activities. Institutional structure does not automatically guarantee efficient supervision. Efficient supervision is based on an independent and transparent institution, staffed with quality employees and enforcement competences, supporting financial market development.
Keywords: G18; G2; 650; Financial markets; Financial conglomerates; Financial supervision; Integration of supervision